Cointegration And Causality Between Insurance Activity And Economic Growth In Morocco - Mouloudi, Abdelaali (جامعة الوادي - University of Eloued, 2020)
This paper is an attempt to study the effect of insurance services on economic growth and causality between both of them in Morocco using time series data for the period 1980-2017 where Augmented Dicky-Fuller test, Johansen cointegration test and Granger causality test are used. The unit root test exhibited that the two time series have a unit root at level and are stationary at the first difference. After implementing Johansen cointegration test, it was found that there is a long run relationship between insurance sector and economic growth. The long run link leads to check the direction of causality. The Granger causality test shows significant bidirectional causality between total insurance premiums and real gross domestic product. These findings accentuate the importance of insurance sector in promoting economic growth.
مقال
Keywords: insurance services ; Augmented Dicky-Fuller test ; Johansen cointegration test ; Granger causality test